Penentuan Absolute Open Flow Potensial (AOFP) Dan Production Performance Prediction Berdasarkan Well Testing Data Pada Sumur Gas “DI” Lapangan “LA” - Nugroho Marsiyanto; M. Mahlil Nasution; Siti Fadillah (Jurnal Bhara Petro Energi, 2024)
In a well that has been drilled (exploration), a hydrocarbon well testing process needs to be carried out, namely well testing. The purpose of well testing is to determine reservoir parameters and to determine the production capacity of a layer or formation. The "DI" gas well in the "LA" field is located in the Batu Raja Formation layer in South Sumatra which is a new well and was drilled in 2010 and well testing was carried out in 2013. The pressure analysis carried out on the "DI" gas well was a deliverability test with back pressure method or flow after flow test, this test is used to determine the maximum value that can be produced by this well. Calculations carried out in this analysis used Microsoft Excel. The Absolute Open Flow Potential (AOFP) value for the "DI" gas well based on analysis of deliverability test results is 5,290 Mmscfd with an exponent (n) value of 0.93 and the C value obtained from constant flow is 5,361 Mmscfd.